Combined actinomycotic and pseudoactinomycotic radiate granules in the female genital tract: description of a series of cases. Issue 12 (27th November 2009) - Boyle, D P; McCluggage, W G
Abstract : Background: Both actinomycotic granules and pseudoactinomycotic radiate granules (PAMRAGs) occur in the female genital tract, most commonly in the endometrium. It is important to distinguish between these since the former may result in pelvic inflammatory disease and require antibiotic treatment while the latter is non-infectious and does not require specific treatment. Aims: To investigate the coexistence of actinomyces-like organisms and PAMRAGs in the same granules, and describe the presence of PAMRAGs in the cervix and the vulva. Methods: Six cases with actinomyces-like organisms and PAMRAGs in the same granules (four in the endometrium, one in a tubo-ovarian abscess, and one in both the endometrium and a tubo-ovarian abscess) are reported as well as seven examples of PAMRAGs in the cervix and one in a vulval abscess. Results: The combined granules consisted of central basophilic Gram and silver positive filamentous organisms consistent with actinomyces surrounded by radiating eosinophilic club-like formations which were Gram and silver negative, the latter consistent with PAMRAGs. The PAMRAGs in the cervix and vulva consisted entirely of Gram and silver negative radiating eosinophilic club-like formations. Conclusions: Although actinomycotic granules and PAMRAGs are distinct lesions which should be distinguished for patient management, they may coexist in the same granules. It is likely in such cases that the PAMRAGs form around the bacterial colonies which act as a nidus. The presence of radiating eosinophilic club-like formations characteristic of PAMRAGs does not preclude the presence of actinomyces. Careful morphological examination plus supportive Gram and silver stains, if necessary, allows the diagnosis of these combined granules. PAMRAGs also occur in the cervix, where it is likely that they form secondary to encrustation of inspissated mucus, and in the vulva.